Nilai-Nilai Pendidikan Dalam Novel Fres Grand Karya Laili Mutamimmah - Aprilia, Puja; Wardarita, Ratu; Misriani, Misriani (Indonesian Research Journal on Education, 2022)
Character education is an effort to help the development of a child's soul, both physically andmentally, from its natural nature towards a humane and better civilization. The purpose of this study in general is to find out and describe the value of character education contained in the Fresh Grad novel by Laili Mutamimmah. Character education in this study can be used as an education that teaches how a special personality must be possessed by a person, so that there is a kind of difference between individuals and other individuals. The research method used is a descriptive method with a qualitative research form. The focus in this study is the value of character education contained in Laili Mutamimmah's Fresh Grad novel, while the subfocus is examining the values of charactereducation through the characterization of the characters contained in Laili Mutamimmah's FreshGrad novel. The data were analyzed using documentation techniques, and from this analysis,conclusions can then be drawn. The results showed that this study analyzed the value of character education in Laili Mutamimmah's Fresh Grad novel, with the results that there were 11 character education values in Laili Mutamimmah's Fresh Grad novel which included: (1) religious, (2) honest, (3) hard work, (4) responsible, (5) disciplined, (6) confident, (7) creative, (8) independent, (9) curious, (10) helpful, (11) tough.